Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858060
|View full text |Cite
|
Sign up to set email alerts
|

Computationally Mediated Pro-Social Deception

Abstract: Deception is typically regarded as a morally impoverished choice. However, in the context of increasingly intimate, connected and ramified systems of online interaction, manipulating information in ways that could be considered deceptive is often necessary, useful, and even morally justifiable. In this study, we apply a speculative design approach to explore the idea of tools that assist in pro-social forms of online deception, such as those that conceal, distort, falsify and omit information in ways that prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Design activities may be used to engage stakeholders; designers, researchers, and stakeholders create or discuss design concepts together to understand stakeholders' experiences and concerns about privacy [67,80,121]. Relatedly, technology probes or conceptual design artifacts can be shared with stakeholders to understand how privacy arises in the context of their daily activities [95,114]. Design sketches and conceptual designs can help researchers analyze empirical data, teasing out perceptions and concerns about privacy [68].…”
Section: Purpose: How Privacy Is Addressed By Designmentioning
confidence: 99%
“…Design activities may be used to engage stakeholders; designers, researchers, and stakeholders create or discuss design concepts together to understand stakeholders' experiences and concerns about privacy [67,80,121]. Relatedly, technology probes or conceptual design artifacts can be shared with stakeholders to understand how privacy arises in the context of their daily activities [95,114]. Design sketches and conceptual designs can help researchers analyze empirical data, teasing out perceptions and concerns about privacy [68].…”
Section: Purpose: How Privacy Is Addressed By Designmentioning
confidence: 99%
“…Recently, HCI community recognized that designers may be allowed to design for a benevolent deception [Adar et al 2013], and that people commonly modulate what they share online [Hancock et al 2009]. Van Kleek et al [2016] explicitly argued for a design capable of assisting users in pro-social forms of online deception. O' Kane, Rogers, & Blandford [2015] noted how people can hide their health tracking devices in uncertain social situations or show them off to achieve a purpose, framing these phenomena in Goffman's theatre metaphor of onstage and offstage behavior [Goffman, 1959].…”
Section: Design For Self-presentationmentioning
confidence: 99%
“…Another study of obfuscation, focusing on the tracker BlueKai (owned by Oracle), found that injecting just 5% fake traffic in addition to real traffic is enough to meaningfully alter the interest profile a tracker compiles about a user [129]. While such deceptive practices may appear malicious, Van Kleek et al argue that there are many potentially beneficial uses of what they call computationally mediated pro-social deception [130]; tricking the trackers might therefore be considered within the category of 'benevolent deception'.…”
Section: Tracker Blocking and Obfuscationmentioning
confidence: 99%